The Assessment of Spinal Alignment Based on a Computer-Assisted Electromechanical Device - Khalifa, Israa; Ghazwan, Aseel; Mahmood, Luay Asaad (Al-Nahrain Journal for Engineering Sciences, 2024)
Spinal alignment examination procedures are frequently employed to assess spinal deformities. The spine plays a crucial role in maintaining the biomechanical functionality of the skeletal system. It protects the spinal cord and facilitates movement, among other vital functions. Various methods, including radiography and non-invasive techniques such as goniometer, inclinometer and kyphometer, have been employed to assess spine alignment qualitatively. Nevertheless, these methods are characterized by a high radiation dose and require significant time. Consequently, this study aimed to develop and create a portable, user-friendly, radiation-free computer-assisted electromechanical device to assess spinal deformities. This device is designed to evaluate sagittal spinal alignment by estimating the angle between two vertebrae for the segmental and global thoracic and lumbar regions, and the length of the spine. This study highlighted the importance of the method in evaluating spinal alignment. The MPU-6050 sensor was employed to record the angle between the two vertebrae, while the rotary encoder was utilized to measure the length of the spine. Subsequently, the data was transmitted to a computer over a Bluetooth module connection, following processing by the Arduino Nano microcontroller. The proposed system was employed on five healthy adult subjects to evaluate their standing posture in the sagittal plane, namely in the upright, flexion, and extension positions. The resulting parameters that define spinal alignment are provided. The suggested system offers the benefits of simplicity, portability, and cost-effectiveness, allowing for rapid and accurate assessment of sagittal spinal alignment. It enables quick clinical assessment and provides few health risks to the patient, leading to correct diagnosis.